History of Phraseological Units and Their Importance in Improving Communicative Skills in Learning A Foreign Language - qizi, Namozova Kamola Bobir; Habibovna, Usmonova Zarina; Tolibovna, Yadgarova Zebiniso; Jumaniyozovna, Bobojonova Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
It is known that the independence of our country has led to tremendous positive changes in the cultural life of the Uzbek people.Thanks to independence, our national values were restored and our people’s spiritual, cultural, moral beliefs filled with national spirit and content.Such achievements have also been reflected in education. There is a wide range of opportunities to pursue any course of stud. In particular, the decision of the first President of the Republic of Uzbekistan on December 10, 2012 "On measures to further improve the system of learning foreign languages" confirms our opinion.According to the decision, in the country Law of the Republic of Uzbekistan “On Education” and a comprehensive system of teaching foreign languages to implement the National Program for Personnel Training; in other words, a system of upbringing of harmoniously developed, educated, modern-minded young generation has been created to further integrate the republic into the world community.[6]